“Nobody Taught Me to Read the Air": Housing, belonging, and religious adaptation among Muslim international students in Japan - Rifki, Hafsa (Journal of International Students, 2026)
This study explores how university housing influences cultural adaptation and belonging among Muslim international students in Japan. Positioned within a higher education setting characterized by indirect communication, standardized residential facilities, and limited institutional acknowledgment of religious differences, the research uses a qualitative, multimethod approach that includes autoethnography, semistructured interviews, and spatial analysis. The findings reveal that dormitories serve as important socio-spatial environments in which religious practices, daily routines, and social interactions are continually negotiated. Four interconnected themes emerged: managing halal food practices in shared kitchens, modifying spaces for ritual cleanliness and prayer, personalizing uniform rooms, and developing peer networks as informal support systems. The analysis demonstrates that seemingly neutral housing designs shift the burden of adaptation onto students.